Frequency scaling of rain attenuation from 23- to 38-GHz microwave signals for reliable communication system - Islam, Md. Rafiqul (Penerbit UTM, 2008)
The most fundamental obstacle encountered in the design of communication systems at millimeter waves is attenuation due to rain. Frequency scaling models provide an alternative to rain attenuation models when data are available for a site. These methods are extremely useful since they tend to be excellent predictors, and provide a means for determining what to expect at a frequency for which there is no data. This paper reports the results obtained from the investigation of frequency scaling of rain attenuation models using one year rain attenuation data measured at 23, 26 and 38 GHz in Malaysia Frequency scaling of rain attenuation from 23- to 38-GHz microwave signals measured in Malaysia.